Meta-Analysis on the Association of Neuropeptide Y rs16139 Variant With the Risk of Alcoholism - Chen, Biqing; Yadav, Manish; Mulkalwar, Madhubala; Saikrishna, Lakkakula; Verma, Henu; Ye, Weibing; Bhaskar, L. V. K. S. (Frontiers in Psychiatry, 2021)
Introduction: The neuropeptide-Y (NPY) is involved in the development of alcoholism through NPY receptors. A T>C mutation causes substitution of leucine to proline at codon 7 (L7P; rs16139) in the signal peptide of neuropeptide Y is known to cause a 42% increase in plasma NPY levels. Studies that analyzed the association between NPY rs16139 and alcoholism risk did not demonstrate conclusive evidence for this relationship. The present study aims to evaluate the association between NPY gene rs16139 variant and alcohol dependence. Method: An electronic search of databases including PubMed and Google Scholar was performed to retrieve studies investigating the association between NPY rs16139 and alcoholism. The pooled odds ratio (OR) with 95% confidence interval (CI) was calculated in allelic and dominant genetic models. Sensitivity analyses and publication bias were assessed in our meta-analysis. The meta-analysis was conducted using the MetaGenyo web tool. Result: Significant heterogeneity was observed across studies (p < 0.001). Our results have shown that there is no significant association between NPY rs16139 variant and the risk of alcoholism in allelic (OR = 0.98, 95% CI 0.70-1.38, p=0.921) and dominant models (OR = 0.98, 95% CI 0.69-1.40, p=0.919). Begg's funnel plot and Egger's test have not shown publication bias (p=0.332). Conclusion: To the best of our knowledge, this is the first meta-analysis that evaluates the relationship between the NPY rs16139 polymorphism and the risk of alcoholism. Our large-scale meta-analysis suggests that NPY rs16139 polymorphism is not associated with alcoholism. However, further studies are needed to increase our understanding of the relationship between NPY variants in alcoholism.